Outcomes and Complications of Total Joint Arthroplasty in Heart Transplant Recipients: A Systematic Review - Alexandros Koskiniotis; George A. Komnos; Antonios Koutalos; Michael Hantes; Theofilos Karachalios; Sokratis Varitimidis; Nikolaos Stefanou (Journal of Clinical Medicine, 2026)
Background: Heart transplantation has evolved into a life-saving intervention for thousands of patients with end-stage disease worldwide. Advances in surgical techniques and immunotherapy have increased life expectancy in this specific patient group, resulting in the emergence of degenerative diseases such as osteoarthritis. Concurrently, due to the frequent administration of corticosteroids to transplant recipients, the rates of joint osteonecrosis remain high. This review aims to evaluate the final functional outcomes as well as the complications of patients with a history of heart transplantation who underwent total hip, knee, or shoulder arthroplasty. Methods: A systematic review of the literature was conducted according to PRISMA guidelines. The primary objective of the study was the improvement of various functional scores at the final clinical follow-up, as well as the recording of postoperative complication rates. Results: A total of 19 retrospective studies were included in the review, including small case series. Among the studies specifically evaluating functional outcomes, patients demonstrated statistically significant improvement in final clinical scores and quality of life. However, regarding complication rates, 12 out of the 19 articles identified a higher ratio compared to the general population, involving either systemic (e.g., renal failure), musculoskeletal (periprosthetic fracture, infection), or cardiac-related adverse events concerning the graft. Conclusions: According to the data analyzed in this systematic analysis, total arthroplasty of major joints demonstrates consistent potential to significantly improve the daily life and functional status of transplant patients. However, evidence regarding overall safety remains heterogeneous.